The Pemberian Keterampilan Budi Daya Ikan dalam Ember (Budikdamber) di Kelurahan Saoka, Tanjung Kasuari, Kota Sorong - Agung Setia Abadi; Ernawati Ernawati; Intanurfemi Bacandra; Hismayasari Hismayasari; Mohammad Sayuti; Achmad Sofian; Kadarusman Kadarusman; Achmad Suhermanto; Saidin Saidin (Institut Pertanian Bogor, 2022)
The Covid-19 pandemic that occurred in Indonesia and even the world caused a decline in people’s income because several work sectors experienced disruption. The aim of providing fish farming skills in buckets (Budikdamber) will be an alternative source of income for the people of Saoka Village, Tanjung Kasuari, Sorong City in the midst of pandemic. A site survey was conducted to determine the place and to find participants in the activity. The service process is carried out in two stages, namely The provision of Budikdamber material is carried out online, while the practice of making Budikdamber is carried out offline. A total of 1200 catfish were stocked in 6 buckets which reselted in a total fish survival rate of 60%. The results obtained by catfish that are kept are able to live and grow even though there is death in the fish. After four months of rearing. The fish can be sold whit a yield of 112 kg whit a selling price of IDR 35,000/kg, whit a total income of IDR 3,920,000. This shows that the tarining is able to provide an alternative source of income for the people of Saoka Village.